Verify the following (i) (-21)×[(-4)+(-6)]=[(-21)×(-4)]+[(-21)×(-6)]
Answers
Answered by
3
HELLO FRIEND...........
Using distributive property of multiplication over addition we can solve it,
(-21) × {(-4)+(-6)} = {(-21)×(-4)}+{(-21)×(-6)}
-21 × -10 = 84 + 126
210 = 210
HOPE IT HELPS U.........
THANK U
Answered by
0
Answer:
it is equal
210=210
Step-by-step explanation:
hope u understand
mark me
follow
Similar questions
Geography,
5 months ago
Math,
5 months ago
Computer Science,
5 months ago
Science,
11 months ago
Math,
11 months ago